A review on operation and maintenance of hydropower plants. (February 2022) - Kumar, Krishna; Saini, R.P.
Abstract: Hydropower is one of the renewable energy sources having the highest conversion efficiency than other renewable energy sources. The hydro turbine is considered as the main component of a hydropower plant and operation and maintenance of various components are the critical issues for optimal energy generation. Under the present paper, a comprehensive literature review on the operation and maintenance aspects of hydropower plants have been presented. In the literature, it has been reported that erosion and cavitation are the main causes of hydro turbine damage and efficiency loss and with the modification of turbine runner blade profile, more than 30% reduction in the impact of sediment erosion can be obtained. In the case of Dam monitoring, the coaxial rotating smeared crack method was found to be more accurate than the conventional method by 32% and 25% for computation of overall tensile and compressive stresses, respectively. Further, various condition-based monitoring techniques such as Fuzzy logic, AHP, PSO, ANN, and SOM have been used to optimize the operation and maintenance of hydropower plants. However, SCADA, IoT, and cloud computing-based monitoring systems can be used for remote monitoring and fault analysis for optimal operation of hydropower plants.